IMPLEMENTASI UNDANG-UNDANG NOMOR 20 TAHUN 2001 TENTANG TINDAK PIDANA KORUPSI PERSPEKTIF KEPASTIAN HUKUM (Universitas Suryakancana, 2021)
Efforts and protection for all nations and bloodshed through existing legal instruments are absolute things, there is no meaning in the words